2022
DOI: 10.3389/fneur.2022.984824
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship among obesity and body fat distribution and epilepsy subtypes

Abstract: ObjectiveThe observational studies indicate an association between obesity and epilepsy, but it is unclear whether such an association responds to causality. The objective of this study was to determine the causal relationship between obesity and fat distribution and epilepsy subtypes based on waist circumference, hip circumference (HP), waist-hip ratio (WHR), and body mass index (BMI).MethodsA two-sample Mendelian randomization study was conducted separately for the four indicators of obesity and epilepsy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A recent prospective study concluded an association between obesity and idiopathic generalized EP and a family history of EP, but not drug-resistant EP 119 . A MR analysis investigated the relationship between obesity, institutional distribution, and EP subtypes and found that obesity, a risk factor for EP, can lead to an increased risk of spasmodic seizures in adolescents, while a high BMI raised the risk of cataplectic seizures in children 120 . Early studies identified the possibility of co-morbidity between EP and obesity, suggesting a risk of obesity-induced EP 121 123 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective study concluded an association between obesity and idiopathic generalized EP and a family history of EP, but not drug-resistant EP 119 . A MR analysis investigated the relationship between obesity, institutional distribution, and EP subtypes and found that obesity, a risk factor for EP, can lead to an increased risk of spasmodic seizures in adolescents, while a high BMI raised the risk of cataplectic seizures in children 120 . Early studies identified the possibility of co-morbidity between EP and obesity, suggesting a risk of obesity-induced EP 121 123 .…”
Section: Discussionmentioning
confidence: 99%
“…Assumption 1 (Relevance), SNPs significantly (P<5E-08) associated with asthma. Assumption 2 (Independence), SNPs not associated with confounding factors that correlated with both asthma and epilepsy, including atopic dermatitis ( 13 ), celiac disease ( 14 ), inflammatory bowel disease ( 15 ), rheumatoid arthritis ( 16 ), hypothyroidism ( 17 ), migraine ( 18 ), multiple sclerosis ( 19 ), educational attainment ( 20 ), and body mass ( 21 ). Assumption 3 (Exclusivity), SNPs affected epilepsy susceptibility directly through asthma and are not associated with epilepsy (P>1E-05).…”
Section: Methodsmentioning
confidence: 99%